2015
DOI: 10.1103/physrevlett.114.084101
|View full text |Cite
|
Sign up to set email alerts
|

Theory for the Spatiotemporal Dynamics of Domain Walls close to a Nonequilibrium Ising-Bloch Transition

Abstract: We derive a generic model for the interaction of domain walls close to a nonequilibrium-Bloch transition. The universal scenario predicted by the model includes stationary Ising and Bloch localized structures (dissipative solitons), as well as drifting and oscillating Bloch structures. Our theory also explains the behavior of Bloch walls during a collision. The results are confirmed by numerical simulations of the Ginzburg-Landau equation forced at twice its natural frequency and are in agreement with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In addition to the type-I LSs, a large variety of type-II LSs also formed through locking of DWs connecting the equivalent states −A + with A + . These states exist for a wider range of parameters in region II and III b and may undergo nonequilibrium Ising-Bloch transitions [58], resulting in complex dynamics [59]. We have shown that in region III b , every type-II LS becomes a hybrid state composed of two type-I LSs related by the symmetry A → −A and are separated by L/2.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition to the type-I LSs, a large variety of type-II LSs also formed through locking of DWs connecting the equivalent states −A + with A + . These states exist for a wider range of parameters in region II and III b and may undergo nonequilibrium Ising-Bloch transitions [58], resulting in complex dynamics [59]. We have shown that in region III b , every type-II LS becomes a hybrid state composed of two type-I LSs related by the symmetry A → −A and are separated by L/2.…”
Section: Discussionmentioning
confidence: 84%
“…For high values of ρ, the DWs may undergo nonequilibrium Ising-Bloch transitions [58], resulting in the drifting of LSs, domain oscillations, and complex dynamics that were studied in detail in Ref. [59]. Fig.…”
Section: Bifurcation Structure Of Type-ii Localized Statesmentioning
confidence: 98%
See 1 more Smart Citation
“…When d = 1,ũ (j) (r = 0) vanishes for j odd and scales as u (j) (r = 0) ∼ exp (−λ r ρ) sin (λ i ρ + φ) (A. 13) for j even, where φ is a constant. Since H(r = 0) − H(u − ) is a quadratic form inũ (j) (r = 0), the higher order correction to M due to the oscillatory tail scales as…”
Section: Resultsmentioning
confidence: 99%
“…This PDE possesses an up-down symmetry A → −A and exhibits a parameter regime where the two "equivalent" equilibria ±A 0 related by this symmetry are simultaneously stable. In 1D a codimension-zero family of steady Ising fronts between ±A 0 is generically present, and may undergo a pitchfork bifurcation into traveling Bloch fronts [4]; near this Ising-Bloch transition the domain walls can exhibit rich spatiotemporal dynamics [13]. In Ref.…”
Section: Introductionmentioning
confidence: 98%